Testing parasite 'intimacy': the whipworm Trichuris muris in the European house mouse hybrid zone - Wasimuddin; Bryja, Josef; Ribas, Alexis; Baird, Stuart J E; Piálek, Jaroslav; Goüy de Bellocq, Joëlle (Ecology and evolution, 2016)
Host-parasite interaction studies across hybrid zones often focus on host genetic variation, treating parasites as homogeneous. 'Intimately' associated hosts and parasites might be expected to show similar patterns of genetic structure. In the literature, factors such as no intermediate host and no free-living stage have been proposed as 'intimacy' factors likely constraining parasites to closely follow the evolutionary history of their hosts. To test whether the whipworm, Trichuris muris, is intimately associated with its house mouse host, we studied its population genetics across the European house mouse hybrid zone (HMHZ) which has a strong central barrier to gene flow between mouse taxa. T. muris has a direct life cycle and nonmobile free stage: if these traits constrain the parasite to an intimate association with its host we expect a geographic break in the parasite genetic structure across the HMHZ. We genotyped 205 worms from 56 localities across the HMHZ and additionally T. muris collected from sympatric woodmice (Apodemus spp.) and allopatric murine species, using mt-COX1, ITS1-5.8S-ITS2 rDNA and 10 microsatellites. We show four haplogroups of mt-COX1 and three clear ITS1-5.8S-ITS2 clades in the HMHZ suggesting a complex demographic/phylogeographic history. Microsatellites show strong structure between groups of localities. However, no marker type shows a break across the HMHZ. Whipworms from Apodemus in the HMHZ cluster, and share mitochondrial haplotypes, with those from house mice. We conclude Trichuris should not be regarded as an 'intimate' parasite of the house mouse: while its life history might suggest intimacy, passage through alternate hosts is sufficiently common to erase signal of genetic structure associated with any particular host taxon.
Keywords: Hybrid zones; parasite life history traits; population structure; phylogeography; Mus musculus